English skills for college freshmen - Villanueva, Perla M.; Acurantes, Dolores C.; Makalinao, Angelita P. (Quezon City, Philippines : Katha Publishing Co., Inc., 2002)
This book has two-fold objective. First, it aims to help the student strengthen and refine the language skills he has already learned- listening, speaking, reading, and writing. Second, it hopes to develop in him correct attitudes and values and to keep him abreast with the developments in his ever-changing world.
Unit I. Unchanging values in a changing world -- Unit II. Role models for a changing world -- Unit III. Evolving societies in a changing world -- Unit IV. Scientific breakthroughs for a changing world -- Unit V. Literature.
Includes bibliographical references and index.
Keywords: ENGLISH SKILLS -- COMMUNICATION -- GRAMMAR